URGENSI PENEMUAN HUKUM OLEH HAKIM SEBAGAI UPAYA UNTUK MEWUJUDKAN KEADILAN DAN KEPASTIAN HUKUM DALAM PENANGANAN KASUS PENIMBUNAN MASKER DAN HAND SANITIZER DI MASA WABAH COVID-19 - Febriawan Mahendra; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2020)
Masks and hand sanitizers are items that are very much needed by the community to prevent and protect from the transmission of the Covid-19 Virus. However, the covid-19 outbreak has been used by irresponsible parties to seek profit by hoarding masks which resulted in scarcity of goods on the market. The police made arrests and charged the perpetrators with Law No. 7 of 2014 concerning Trade, however, the two types of goods are not the categories of basic and important goods so that the process of handling hoarding cases does not run properly, resulting in a legal vacuum. The legal consequence of not regulating masks and hand sanitizers in the case of stockpiling as a basic and important item will have implications for the law enforcement process in handling the crime of hoarding masks and hand sanitizers that cannot run optimally. Therefore, there is an urgency that can be taken by law enforcement officials to process hoarding cases through legal discovery by judges in court. In handling this case, the judge must make legal findings through extensive discernment by likening masks and hand sanitizers which are not categorized as essential and important items, but given the situation and conditions of the Covid-19 pandemic which require these two items to be considered or interpreted as important items. with extensive interpretation.